Penentuan Peringkat Bahaya Tsunami dengan Metode Analytical Hierarchy Process (Studi kasus: Wilayah Pesisir Kabupaten Sukabumi) - Oktariadi, Oki (Indonesian Journal on Geoscience, 2009)
http://dx.doi.org/10.17014/ijog.vol4no2.20093Hierarchy structure of a tsunami risk encompasses the study of hazard, vulnerability, and capac- ity factors. The focus of this research is hazard factors, with indicators comprise beach slope, beach coarseness (surface material), run up, and earthquake intensity. Computation method used in the deci- sion system is the Analytical Hierarchy Process (AHP). The AHP method is to determine the weight of indicators and matrices of hazard factor hierarchy. The final total score of the hazard factors will be useful for tsunami hazard mapping through a geographic information system (GIS). It consists of four hierarchies ofÂ  tsunami hazard that are high, middle, low, and safe levels. The coastal regions in Sukabumi having high tsunami disaster risk are the Gulf of Pelabuhanratu, Ciemas plain (Gulf of Ciletuh), Ujung Genteng Cape, and some parts of coastal plain areas in Sim- penan. Those having middle tsunami disaster risk are coastal area of Surade, Cibitung, Tegalbuleud, whereas those having low tsunami disaster risk are Cisolok cliff, Simpenan, and Ciemas cliff area. The other coastal zones are included into a safe area. Â